Cultural evolution and emergent group-level traits through social heterosis. Issue 3 (27th June 2014) - Nonacs, Peter; Kapheim, Karen M.
Abstract: Smaldino proposes emergent properties of human groups, arising when individuals display both differentiation and organization, constitute a novel unit of cultural selection not addressed by current evolutionary theory. We propose existing theoretical frameworks for maintenance of genetic diversity – social heterosis and social genomes – can similarly explain the appearance and maintenance of human cultural diversity (i.e., group-level traits) and collaborative interdependence.